Novel High-Speed Turbo Compressor With Integrated Inverter for Fuel Cell Air Supply - Antivachis, Michael; Dietz, Flurin; Zwyssig, Christof; Bortis, Dominik; Kolar, Johann W. (Frontiers in Mechanical Engineering, 2021)
Fuel cell technology is continuously gaining ground in E-mobility applications. Fuel cells require a constant supply of pressurized air, for which high-speed turbo compressors with air bearings are an optimal choice to reduce size, guarantee oil-free operation required for the lifetime of the fuel cell and increase efficiency. However, the inverter driving the electric motor of the turbo compressor does not scale down with increasing speed, therefore other technology advances are required to achieve an overall compressor system with low weight. New power electronic topologies (double-bridge voltage sources inverter), cutting edge power semiconductor technology (gallium nitride) and multi objective optimization techniques allow to reduce the inverter size, increase inverter efficiency and improve the output current quality and in return lower the losses in the electric motor. This enables the electrical, mechanical and thermal integration of the inverter into the compressor housing of very high-speed and compact turbo compressors, thereby reducing size and weight of the overall compressor system by a factor of two. Furthermore, a turbo compressor with integrated inverter reduces complexity and cost for operators by savings in casing, cables, coolant piping and connectors, and reduces EMI noise by shielding the high frequency motor currents with one housing. Beside its main application for fuel cell air supply, the advantages gained by an integrated inverter can also be used in other boosting and air handling applications such as advanced air and exhaust handling in combustion engines. The proposed integration concept is verified with a 280,000 rpm, 1 kW turbo compressor, targeted for the balance of plant of a 5-15 kW fuel cell. The experimental results show that the temperature limits on the power electronics parts can be kept below the limit of 90°C up to a coolant temperature of 55°C, and besides the advantage of lower cabling effort the efficiency of the compressor system (turbo compressor and integrated inverter) is increased by 5.5% compared to a turbo compressor without integrated inverter.